- #1

- 427

- 2

## Homework Statement

1) Simplify the following Boolean expression:

Y = ABCD – ABD

## Homework Equations

## The Attempt at a Solution

I simplified it in the following way:

Y = ABCD – ABD. (C + 1)

= - ABD

But the answer given in my book is ABD.

- Thread starter Amith2006
- Start date

- #1

- 427

- 2

1) Simplify the following Boolean expression:

Y = ABCD – ABD

I simplified it in the following way:

Y = ABCD – ABD. (C + 1)

= - ABD

But the answer given in my book is ABD.

- #2

- 8

- 0

Could be a typo in the back of the book. In my Discrete Math we are finding almost 20 errors per section. =o) Contact your teacher?

- #3

- 2

- 0

Boolean algebra deals solely in ones and zeroes. It has only three operators: addition, multiplication and negation. There can be no negative numbers. Namely, -1 is not an allowed number, so the concept of subtraction is meaningless is Boolean algebra.

Having said that, Y= ABCD – ABD has either a misprint – instead of +. In this case,

Y= ABCD + ABD = ABD(C+1)=ABD(1)=ABD

Or, possibly, – is given some special meaning.

- #4

- 427

- 2

Y = ABD - ABCD

Isn't it?

- Last Post

- Replies
- 7

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 1

- Views
- 3K

- Last Post

- Replies
- 2

- Views
- 734

- Last Post

- Replies
- 3

- Views
- 783

- Last Post

- Replies
- 3

- Views
- 3K

- Last Post

- Replies
- 2

- Views
- 2K

- Last Post

- Replies
- 1

- Views
- 775